Unleashing eve within adam A study on the positive side of the coming out of male homosexuals. - Berdan, Jessica Chisa D.; Dichosa, Robyn Dame N.; Docena, Robbin S. (Jessica Chisa D. Berdan, Robyn Dame N. Dichosa [and] Robbin S. Docena, 2010)
This study aims to identify the factors that facilitated the coming out of male homosexuals, describe their process of coming out, the consequences as well as the advantages and disadvantages after their transition to homosexuality and the positive side that coming out has brought to them. The study includes 13 research respondents who answered a 26-item questionnaire followed by a set of follow up interview questions. The data gathered provided the following results: the major factor which triggered the coming out of male homosexuals was reasons of attraction to individuals belonging to the same sex; majority of the respondents realized that they were homosexuals when they were at the 4-8 and 14-18 years old age category (30.8%); a significant number of respondents found it not that easy and not that hard to accept themselves (38.4%) upon realizing that they were homosexuals; as individuals climb up the developmental ladder and as they grow older, the consequences of coming out is also getting and what awaits them is a much more complicated life as a homosexual; the first major disadvantages that they pointed out were being discriminated and people having sexual biases while the number one advantage that the male homosexuals have pointed out is that they were now able to talk about their sexuality to anyone compared to that when they were just hiding it before. For future researchers regarding this issue, it is recommended for researchers to eliminate all biases towards the subjects' specifically male homosexuals because these would hinder the flow of their study and this would impede their pursuit for significant data.